PENGARUH PROSES PELAKSANAAN PENAGIHAN PAJAK DENGAN SURAT PAKSA TERHADAP PENINGKATAN PENERIMAAN PAJAK DI KANTOR PELAYANAN PAJAK PRATAMA SURAKARTA - Chomsatu, Yuli (PARADIGMA, 2009)
Compulsion Letter is a letter of instruction to pay the tax and tax collection cost. With this letter, it is hoped that taxpayers who has back tax will paid off their back tax. This research aimed :(1) to know the influence of compulsion letter amount published toward the improvement of taxâs acceptance, (2) to know the influence taxpayers amount who activelly pay off the back tax toward the improvement of tax acceptance, (3) to know the influence of compulsion letter amount publised and taxpayers amount who actively pay off the back tax simultaneous toward the improvement of taxâs payment.This research uses survey research. Population and sample in this reseach is the employees of Tax Service Office of Pratama Surakarta as 55 employees. Data is collected by the researcher using questionaire about the amount of compulsion letter publised, taxpayer who actively pay off the back tax and the improvement of tax acceptance. Data analized by using double linier regresion, t test and F test. The analysis result shows that: (1) the compulsion letter amount variable published does not influence and significant toward the improvement of tax acceptance, (2) the taxpayers who activel pay off the back tax variable influence and significant toward the improvement of tax acceptance, (3) the compulsion letter amount published variable and taxpayers who actively pay off the back tax simultaneous has significant influence toward the improvement of tax acceptance.Â Key Word :Â Compulsion Letter, Â pay the tax and tax collection cost.Â